IMPLEMENTASI MEDIA PEMBELAJARAN ZOOM MEETING TERHADAP MINAT BELAJAR MAHASISWA SEKOLAH TINGGI TEOLOGI DUTA PANISAL JEMBER - Gusuli Ndruru; Tri Wurianingsih Laksono (Metanoia, 2022)
Online learning is a solution for the limited learning activities during the current pandemic. Internet-based distance learning media is the right choice to replace face-to-face learning, including video conferencing such as Zoom Meetings. Online lectures need to be packaged in an innovative way to attract students interest in learning. Interest is a strong source of motivation in learning and triggers one's participation/activity. This is the background of the author to conduct research with the title "Implementation of Zoom Meeting Learning Media on Learning Interests of STT Duta Panisal Students, Jember." This study aims to determine the implementation of the Zoom Meeting learning media on the learning interest of STT Duta Panisal students. The methodology used is qualitative to study, analyze and describe the data as a whole. The approach is a case study, to explore facts through detailed, in depth data collection involving various sources of information, such as observations, interviews, and reports. Sources of data were obtained from observations and in-depth interviews using questions that were prepared and developed during interviews with 8 students and 4 lecturers of online learning. The results showed that Zoom Meeting was quite well used as an online learning medium, although some students still felt uncomfortable. Among them are noisy atmosphere, less stable internet signal, as well as the existence of courses that are presented "marathon" in a short period of time. An attitude as if "nobar" causes a "mental block", an impact on the low acceptance of information. For lecturers, online learning is a solution if they are unable to attend, even though there are internet connection barriers. Students interest in learning during online learning is quite good, but not yet comparable to changes in cognitive behavior. Remembering and affirming to yourself the purpose of studying at STT is a way for students to ignite their interest in learning. Lecturers use various ways to stimulate students interest in learning, provide words of encouragement/motivation. Two-way communication between lecturers and students is a form of cooperation that is indispensable, including the openness of students when they have difficulty understanding the material.